2020
DOI: 10.1155/2020/2861240
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Neoantigens in Colorectal Cancer as Potential Immunotherapy Targets

Abstract: This study was aimed at investigating the mutations in colorectal cancer (CRC) for recurrent neoantigen identification. A total of 1779 samples with whole exome sequencing (WES) data were obtained from 7 published CRC cohorts. Common HLA genotypes were used to predict the probability of neoantigens at high-frequency mutants in the dataset. Based on the WES data, we not only obtained the most comprehensive CRC mutation landscape so far but also found 1550 mutations which could be identified in at least 5 patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Thus, the patients' cytotoxic properties seemed consistent with the mutational and clinical course of the neoplastic progeny. The mutated KRAS G12D and G12V have been reported as recurrent neoantigens in CRC, and this supports the hypothesis about the role of immune-mediated clonal selection in the above patients (20), which deserves further studies to be definitely addressed.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, the patients' cytotoxic properties seemed consistent with the mutational and clinical course of the neoplastic progeny. The mutated KRAS G12D and G12V have been reported as recurrent neoantigens in CRC, and this supports the hypothesis about the role of immune-mediated clonal selection in the above patients (20), which deserves further studies to be definitely addressed.…”
Section: Discussionsupporting
confidence: 78%
“…found that indel-related neoantigens covered a large proportion of MSI-H CRC patients. 35 About 10 to 20 neoantigen peptides are usually synthesized simultaneously to prepare vaccines or other immunotherapy products. 10 Jitske et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that single-nucleotide variants (SNVs) in genes, such as KRAS, PIK3CA, PCBP1, and CHEK2, are associated with the production of the 10 most frequent neoantigens. An analysis of the published CRC WES data has enabled a more complete map of CRC mutations to be produced, which indicated that high-frequency mutations such as KRAS G12D, KRAS G12V, PIK3CA E545K, PIK3CA H1047R, and BMPR2 N583Tfs ∗ 44 can combine with HLA and be presented [ 68 ]. However, recent findings indicate that this selection of mutated driver genes may have weak binding affinity with MHC molecules during the development of tumors.…”
Section: Neoantigens and Immune Response In Colorectal Cancermentioning
confidence: 99%